Comparison of Madden-Julian oscillation in three super El Niño events - Lifeng Li; Xiong Chen; Chongyin Li; Chongyin Li; Xin Li; Minghao Yang (Frontiers in Earth Science, 2023)
This paper investigated the characteristics of Madden-Julian Oscillation (MJO) in three super El Niño events (i.e., 1982/83, 1997/98 and 2015/16 El Niño events) based on reanalysis data. MJO with apparent eastward propagation can be observed during the developing stages of these three super El Niño events. Enhanced MJO zonal wind was observed over the western Pacific, especially in 1997/98 and 2015/16 El Niño events, which is mainly attributed to the effects of tropical background circulation and extratropical anomalous circulation. During the mature stages of 1982/83 and 1997/98 El Niño events, MJO with noticeable eastward propagation cannot be observed, and the MJO zonal wind amplitude at 850 hPa was weakened (enhanced) over the Indian Ocean and western Pacific (central and eastern Pacific). However, MJO zonal wind amplitude over the central and eastern Pacific was enhanced and the prominent eastward propagation was also found in the mature stage of 2015/16 El Niño. The eastward propagation of MJO was also observed during the decaying stages of the three super El Niño events, but its intensity was weaker compared with the developing and mature stages. The abnormal activity of MJO during the mature and decaying stages may be closely related to the characteristics in circulation and moisture anomalies caused by El Niño and the seasonal cycle of circulation and moisture. In addition, this study found that the RMM index and MJO zonal wind amplitude may lead to contradictory results in identifying the characteristics of MJO activity, especially during the developing and decaying stages.